Can ancestry be consistently determined from the skeleton? - Sierp, Ingrid; Henneberg, Maciej (Anthropological Review, 2015)
Although the concept of race has been thoroughly criticised in biological anthropology, forensic anthropology still uses a number of methods to determine the ‘race’ of a skeleton. The methods must be evaluated to see how effective they are given large individual variation. This study used 20 cases of skeletons of varied provenance to test whether the nine published methods of ‘race’ determination, using a range of various approaches, were able to consistently identify the ethnic origin. No one individual was identified as belonging to just one ‘major racial class’, e.g. European, meaning that complete consistency across all nine methods was not observed. In 14 cases (70%), various methods identified the same individual as belonging to all three racial classes. This suggests that the existing methods for the determination of ‘race’ are compromised. The very concept of ‘race’ is inapplicable to variation that occurs between populations only in small ways and the methods are limited by the geographic population from which their discriminant functions or observations of morphological traits were derived. Methods of multivariate linear discriminant analysis, e.g. CRANID, are supposed to allocate an individual skull to a specific population rather than a ‘major race’. In our analysis CRANID did not produce convincing allocations of individual skeletons to specific populations. The findings of this study show that great caution must be taken when attempting to ascertain the ‘race’ of a skeleton, as the outcome is not only dependent on which skeletal sites are available for assessment, but also the degree to which the unknown skeleton’s population of origin has been investigated.